INSTITUTIONS AND INDUSTRIAL DEVELOPMENT IN SABAH - Firdausi Suffian; Kasim Mansur; Ika Suzieana Jamluddin; Arnold Puyok; Azmi Abdul Majid (International Journal of Accounting, Finance and Business, 2022)
Industrialisation has been and continues to be lynchpin to modernise a stateeconomy. Here, configuration of industrial policy is central in expanding and diversifying thedownstream activities. Coherent industrial policy implementation depends upon the role ofinstitutions that shape and facilitate elite policy makers in configuring and defining policypriority. It is important to note that institutions for every state differs significantly, this is dueto the historical specificity, political events, norms that formed institutions. The institutionalsettings can condition policy actor defines interest and priority differently. In the case of Sabah,although the state is rich in resources, the implementation of industrial policy seems to be littlesuccess. The existing state’s economic structure does not support the expansion of downstreamindustry. The state continues to focus on resource extraction activities instead of moving up thevalue chain in the industrial sectors. This structural deficiency can be attributed to ineffectiveinstitutions which hinder coherent industrial policy implementation. Given the limitedindustrial development and policy-implementation gap, the state has fallen behind in manyaspects of economic development.